Analysis of the Peaks in the Bucegi Mountains, With Relevance for Sports Tourism Activities - Ioan BÎCA (Studia Universitatis Babeş-Bolyai: Educatio Artis Gymnasticae)
Mountain peaks are geographical landmarks that arouse the interest of tourists practicing mountain tourism activities. Summiting a peak is an important reason, both for the views it offers over the landscape and for the personal satisfaction of reaching that point, which requires fitness and will. In addition to the recreational approach, the peaks can also be analyzed from a geo-morphometric point of view, concerning their shape, altitude, and prominence, aspects that matter in sports tourism activities. In this context, the present work aims to analyze the peaks of the Bucegi Mountains and establish their prominence. It is also aimed at the practical side of the problem, materialized through the methodological approach included in the research.